Diagnostic, prognostic and therapeutic potential of 6-minute walk test in patients with heart failure - A. V. Budnevsky; A. Ya. Kravchenko; R. E. Tokmachev; T. A. Chernik; E. V. Tokmachev; Yu. B. Letnikova (Кардиоваскулярная терапия и профилактика, 2020)
The six-minute walk test (6MWT) is a well-known exercise test used in medical practice to assess the functional status of patients with various chronic cardiovascular and respiratory diseases. The results of modern research describe new potential of 6MWT, which allow a more accurate interpretation and predict the course of diseases. Heart failure (HF) is the outcome of many structural and functional heart disorders. To improve the prognosis of patients with HF, early diagnosis, appropriate therapy and effective control of the disease course are important components. This review describes the diagnostic, prognostic and therapeutic potential of 6MWT in patients with HF.